Peningkatan Kualitas Pembelajaran Melalui Pendekatan Konstruktivistik dalam Pendidikan bagi Anak Usia Dini - Sulthon, Sulthon (THUFULA, 2013)
Education is a conscious effort made by adults to change behavior more positive and meaningful. Behavioral changes need to hold a variety of serious and continuous efforts through meaningful learning. Meaningful learning will be ableto make changes concerning the behavior of cognitive, affective and psychomotor.Learning which is able to achieve all of the three domains of educational objectivesis an active learning model that is performed to build their own knowledge throughteacher designed-learning activities. Constructivist learning is learning that is capable of changing the old style of teaching where the teacher is always an active role or be a style of teaching where the teacher as a facilitator who designed learning by activating his students to learn on their own, learn to interact in a responsible group for achieving learning outcomes individually, while he provides guidance and facilitates them to learn.